The Analysis of The Push Pull Motivation Factor and The Expectation of International Tourist in Ramayana Ballet Prambanan Yogyakarta - Momentya Irsha (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2018)
Cultural attraction in a country or region is an attraction that is demanded by international tourist, because tourists obviously want to know the culture of that country, such as by watch the dance. Ramayana Ballet Prambanan is a dance presents Javanese culture, both Central Java and Yogyakarta Special Region. This performance tells about Ramayana that is illustrated on the relief of Prambanan Temple. This study analyzes the push and pull factors of motivation, and expectation. Respondents of this study is international tourists. The writer adapted the push and pull factor developed by Crompton (1979), and suited by the condition of Ramayana Ballet Prambanan. The method used by the writer is interview with 65 respondents. While, expectation theory is adapted from Oliver (1980) through questionnaire method with 100 respondents. Furthermore, for the analytical purpose of this research, the data is analyzed by using SPSS 20 with descriptive analysis. The result showed that the push factor motivation of international tourist is new experience, and the pull factor is the attractiveness of Javanese culture. In addition, the biggest expectation of international tourist is cleanliness.